Strategies to Make Methods Based on Flow Injection Analysis Greener. Issue 7 (6th July 2020) - Bezerra, Marcos Almeida; Santelli, Ricardo Erthal; Lemos, Valfredo Azevedo; dos Santos Alves, Juscelia Pereira; Braz, Bernardo Ferreira; Santos, Luana Bastos
Abstract: The implementation of flow injection analysis (FIA) systems and correlated techniques in the laboratory routine provides an increase of analytical throughput and the reduction of risks of analyte losses and contamination. Naturally, it contributes to the reduction of reagent consumption and minimization of waste generation. This paper presents and discusses an overview of the main strategies adopted to make methods based on FIA systems more environmentally friendly, and offers a review of these methods that covers the period from January 2002 to December 2019. Strategies based on reagent management (adoption of procedures without reagents, replacement of toxic reagents, recycling and reuse of reagents and, use of immobilized reagents), the online waste treatment, and the improvements of FIA systems (flow system configurations that avoid reagent wastage, use of green detectors, automation, and miniaturization) are approached in this perspective. Abstract : Flow injection analysis (FIA) systems are efficient and economical for several chemical species determinations of interest in today's world. Strategies to make FIA systems more environmentally friendly are discussed, including reagent management, online waste treatment, and improvements of FIA systems. The review article covers such methods published during the last two decades.